Numerical and experimental investigations on temperature and thermal damage in cortical bone drilling - Mohd Faizal, Ali Akhbar (2020)
Bone drilling is a typical operation in the myriad of surgeries in the orthopedics, oral and maxillofacial, neurological, and otolaryngology. Friction and shear deformation energy during the drilling surgery generates extreme heat in the drilling hole, which increases the bone temperature. Furthermore, the low thermal conductivity of bone escalates the bone temperature and causes the irreversible death of the bone cells (thermal osteonecrosis). Thermal osteonecrosis loosens fracture fixations (orthopedic), tooth implants (oral and maxillofacial), and cochlear implants (otolaryngology), which could cause revision surgeries. These surgeries necessitate additional costs and healing time. Moreover, to add insult to injury, thermal osteonecrosis could even cause permanent disability to the patients when it involves nerve injuries. Drilling parameters (rotational speed, feed, drilling hole depth, and drill bit diameter) and drill bit geometries (point angle, helix angle, and web thickness) have been identified as two main factors that can be manipulated to reduce the bone temperature. Therefore, this thesis aims at reducing the thermal damage in bone drilling by using optimal drilling parameters (ODP) and improved drill bit geometries (IDG). In order to determine the ODP and IDG, approaches including numerical, experimental, and statistical were adopted. Human cortical bone and surgical drill bit models were developed using commercially available finite element method (FEM) software, DEFORM-3D. In terms of drilling parameters, the rotational speed of 50 rev/min to 400,000 rev/min, feed of 0.0100 mm/rev to 0.1875 mm/rev, drilling hole depth of 0.5 mm to 5.0 mm, and drill bit diameter of 0.5 mm to 6.0 mm were investigated. Whereas, for drill bit geometries, the point angle of 60-160°, helix angle of 10-36°, and web thickness of 5-50 % were investigated. The simulation results were validated then with the experimental bone drilling using a conventional milling machine. A new method called sum of weightage was introduced to determine the suitable ranges for optimization study. From the sum of weightage results, the ranges for drilling parameters (rotational speed = 50-500 rev/min and feed = 0.1600-0.1875 mm/rev) and drill bit geometries (point angle = 118°-140°, helix angle = 30°-36°, and web thickness of 10 %-18 %.) for optimization study were selected. Then, the response surface methodology (RSM) and multi-objective optimization studies were performed to determine the ODP and IDG. Results revealed that the ODP could be obtained with a rotational speed of 50 rev/min and feed of 0.1750 mm/rev. Whereas, the optimal surgical drill bit (stainless steel 316L) can be constructed with a point angle of 131.8°, helix angle of 36°, and a web thickness of 11.8 %. The proposed ODP can significantly reduce the thermal damage compared with the recommendations from the previous studies (maximum bone temperature elevation (Tmax) = 8.9–85.8 °C, osteonecrosis diameter (OD) = 5.16 mm-10.07 mm, and osteonecrosis depth (OH) = 3.35-5.50 mm). Furthermore, the IDG can reduce thermal damage more than the existing surgical drill bit (Tmax = 2.3 °C, OD = 1.16 mm, and OH = 1.96 mm). When ODP and IDG are combined, the thermal damage can further be reduced up to 1.2 °C to 9.3 °C for Tmax, 4.45 mm for OD, and 2.22 mm for OH compared with when using ODP and IDG individually. The significant original contributions from this thesis come from several areas. This work has determined the suitable bone model as the replacement for human bone in bone drilling (in terms of temperature elevation). Next, new ODP and IDG were recommended to reduce significant thermal damage. This research extends our knowledge of thermal osteonecrosis prevention and will serve as a base for future studies in the automation of bone drilling surgery.